2004
DOI: 10.1007/s00027-004-0695-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cadmium concentration in water of Lake Chapala, Mexico

Abstract: Watershed management in Mexico is generally carried out based on hydrological information, whereas water quality data are mainly used in the control of wastewater discharges and water uses. Information on toxic contaminants is scarce and expensive to gather. A method was developed to predict inorganic contaminant concentration in Lake Chapala, Mexico, by using hydrological data for water balance, water quality information and analyses, sediment quality monitoring data, and ap- Aquatic Sciencesplying a chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To model trace metal accumulation in the lake (Hansen and van Afferden, 2004) ity standards, ion charge and mass balances were described by the following equations:…”
Section: Ion Balance Estimationmentioning
confidence: 99%
“…To model trace metal accumulation in the lake (Hansen and van Afferden, 2004) ity standards, ion charge and mass balances were described by the following equations:…”
Section: Ion Balance Estimationmentioning
confidence: 99%
“…Regarding the other metal content, the Cd concentration was higher than the monthly and daily average stipulated in Mexican regulations (NOM-001-ECOL-1996) for irrigation water and was present in all water and soil sampling sites in both seasons. The presence of Cd in water during RS was greater than DS, which is generally associated with water levels in the lake and suspended sediments (Asati et al, 2016) as a result of decreasing water levels and the action of waves, Cd may be more susceptible to desorption in contaminated sediments and the increase of various ions (Hansen and Van Afferden, 2004). It was possible to observe the presence of lead in the soil during both DS and RS.…”
Section: Resultsmentioning
confidence: 90%
“…[18] In this study, the distribution of metals between the iron oxy-hydroxides in surface sediments has been evaluated by use of a SCM as sediments are resuspended during storm events, as a function of Redox potential and sorbate/sorbent ratio in a natural river system. For this purpose, a method developed by Hansen and van Afferden [19] was modified to predict metals concentration in the future Arcediano Dam by using information obtained from water and sediment quality sampling and analyses, and applying a chemical equilibrium model to estimate the possibility of an increase in metals concentration. It has been shown that increasing sediment accumulation in the Arcediano Dam could lead to an increase in dissolved metals that, in the future, might affect the quality of water to be purified for human consumption.…”
mentioning
confidence: 99%